2017
DOI: 10.1016/j.neuroimage.2017.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of odorant activity-dependent migration of neural precursor cells and olfactory bulb growth

Abstract: Neural progenitors or neuroblasts are produced by precursor cells in the subventricular zone (SVZ) and migrate along the rostral migratory stream (RMS) to the olfactory bulbs (OB) throughout life. In the OB, these adult born neurons either die or replace existing olfactory interneurons, playing a critical role in the stabilization of OB circuitry. Although several aspects of the addition of new neurons into the OB have been studied, it is unclear whether long-distance activity from the OB can regulate the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Currently, neuroinflammation can be assessed with MRI using injected ultrasmall superparamagnetic particles of iron oxide (SPIO) that are absorbed by macrophages [ 43 , 44 ]. It is known that inflammation-activated microglia and macrophages accumulate ferritin [ 40 ], which, in turn, can be visualized using T2* MRI [ 4 , 5 ]. Although the T2* technique is successfully used in the clinic for detecting iron accumulation in Parkinson’s disease [ 45 ], Alzheimer’s disease [ 45 ], multiple sclerosis [ 45 ], and hemorrhagic stroke [ 46 ], there are no data on application of T2* for imaging neuroinflammation in ischemic stroke in human patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, neuroinflammation can be assessed with MRI using injected ultrasmall superparamagnetic particles of iron oxide (SPIO) that are absorbed by macrophages [ 43 , 44 ]. It is known that inflammation-activated microglia and macrophages accumulate ferritin [ 40 ], which, in turn, can be visualized using T2* MRI [ 4 , 5 ]. Although the T2* technique is successfully used in the clinic for detecting iron accumulation in Parkinson’s disease [ 45 ], Alzheimer’s disease [ 45 ], multiple sclerosis [ 45 ], and hemorrhagic stroke [ 46 ], there are no data on application of T2* for imaging neuroinflammation in ischemic stroke in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is a highly-informative technique, which allows non-invasive visualization of anatomical structures and physiological processes, including neurogenesis, in the body [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Neurogenesis in pathological conditions is a complex process that evolves over time and includes migration of young neurons from neurogenic niches to the lesion site as well as formation of new neurogenic niches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nieman et al (2010) used image registration and intensity-based analysis to identify labeled cells and determine their speed of migration. They estimated that labeled NPCs move at 100–120 μm/h in the RMS and 50 μm/h in the OB (Nieman et al, 2010; Pothayee et al, 2017; Shuboni-Mulligan et al, 2018), slightly slower than the speeds of 150–700 μm/h that were measured in mice with tumors (Elvira et al, 2012). These migration rates are not far from those determined in studies of neurogenesis that employ immunohistochemical methods of detection, which determined a migration rate of 70–80 μm/h in naïve rodents (Nam et al, 2007).…”
Section: Mri Of Endogenous Npcsmentioning
confidence: 90%
“…These migration rates are not far from those determined in studies of neurogenesis that employ immunohistochemical methods of detection, which determined a migration rate of 70–80 μm/h in naïve rodents (Nam et al, 2007). Recently, the technique demonstrated that both environmental stimuli, olfactory activity (Pothayee et al, 2017) and aging (Shuboni-Mulligan et al, 2018) impacted migration rates in vivo . Understanding the dramatic decrease in NPC migration as animals aged is critical, as many diseases that recruit NPC are more prevalent in older individuals (Wang et al, 2013).…”
Section: Mri Of Endogenous Npcsmentioning
confidence: 99%